ENVIRONMENTAL SOCIAL RESPONSIBILITY PRACTICES IN BUSINESSES: CASE STUDY (Third Sector Social Economic Review, 2025)
The concept of social responsibility is a concept that emerged as businesses grew and expanded their sphere of influence after the industrial revolution. Although it dates back to the 1900s, it was only after the 1950s that it entered the agenda of businesses in its current sense. In this period, with the development of mass media, consumers started to see the impact of businesses on society, other businesses, nature and natural resources more. Consumers have started to react and boycott businesses in the face of negative situations they see. This situation has pushed businesses to act responsibly and implement social responsibility practices. Additionally, businesses have had to carry out social responsibility activities in order to be accepted by consumers. In this study, the environmental social responsibility practices of 10 businesses (Opet, Hepsiburada, Albaraka Türk Katılım Bankası, Ziraat Bankası, Toyota, Torku, Eti, Anadolu Hayat Emeklilik, Uğur Derin Dondurucu ve Arçelik) from seven sectors operating in Turkey were examined using the case study method. In the examinations, it was observed that the enterprises emphasized activities and practices such as recycling waste, creating forests through afforestation, using energy efficiently and saving energy (electricity, fuel, etc.), preventing water waste, using environmentally friendly products in offices and production units, saving paper with internet-based applications and new technologies, and reducing carbon dioxide emissions.
Keywords: Social responsibility; environment; case study; marketing research; consumer behaviors